Jesus and the last days the interpretation of the Olivet Discourse - Beasley-Murray, George Raymond, 1916-2000 (Peabody, MA Hendrickson, 1993)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Mark XIII -- criticism, interpretation, etc. -- history; Eschatology -- Biblical teaching